Nanoparticles in the lung and their protein corona: the few proteins that count. Issue 9 (20th October 2016) - Whitwell, Harry; Mackay, Rose-Marie; Elgy, Christine; Morgan, Cliff; Griffiths, Mark; Clark, Howard; Skipp, Paul; Madsen, Jens
Abstract: The formation of protein coronae on nanoparticles (NPs) has been investigated almost exclusively in serum, despite the prevailing route of exposure being inhalation of airborne particles. In addition, an increasing number of nanomedicines, that exploit the airways as the site of delivery, are undergoing medical trials. An understanding of the effects of NPs on the airways is therefore required. To further this field, we have described the corona formed on polystyrene (PS) particles with different surface modifications and on titanium dioxide particles when incubated in human bronchoalveolar lavage fluid (BALF) from patients with pulmonary alveolar proteinosis (PAP). We show, using high-resolution quantitative mass spectrometry (MS E ), that a large number of proteins bind with low copy numbers but that a few "core" proteins bind to all particles tested with high fidelity, averaging the surface properties of the different particles independent of the surface properties of the specific particle. The averaging effect at the particle surface means that differing cellular effects may not be due to the protein corona but due to the surface properties of the nanoparticle once inside the cell. Finally, the adherence of surfactant associated proteins (SP-A, B and D) suggests that there may be interactions with lipids and pulmonary surfactant (PSf), which could have potential in vivo health effects for people with chronic airway diseases such as asthma and chronic obstructive pulmonary disease (COPD), or those who have increased susceptibility toward other respiratory diseases.